Performance variation of a desiccant wheel dehumidifier equipped with a sensible heat exchanger due to experimental fluctuations in regenerative heat input - Dendi Adi Saputra; Yugo Osaka; Takuya Tsujiguchi; Akio Kodama (Case Studies in Thermal Engineering, 2023)
This study investigates the impact of different control strategies on the performance of a single desiccant wheel dehumidifier with a heat recovery in real-world applications. A method to minimize the performance fluctuation as an effect of dynamic system performance response is proposed. First, the effect of regeneration heat input (Qin) changes on the system performance of the above dehumidifier was clarified. Second, the performance behavior was examined in response to transient conditions for different operation modes and was used to determine the most effective operation mode. Qin was assumed to change over time, which would influence the regeneration temperature and airflow velocity. The results showed that fluctuating Qin reduces the dehumidification capacity (ΔX) and coefficient of regeneration performance (COPreg). Therefore, a rotational control speed was implemented in the optimum operation mode, which was effective in preventing the system performance decline and accelerated the emergence of the rotational speed control effect.